Giant dermoid cyst mimicking posterior fossa tumors in a child: A Case Report and Review of the Literature - Leopoldo Mandic Ferreira Furtado; José Aloysio da Costa Val Filho; Bruno Lacerda Sandes; Plínio Duarte Mendes; Patrícia Salomé Gouvea Braga (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: Intracranial dermoid cysts are rare, congenital and, benign lesions. The etiology of these lesions is related to an embryonic defect during neurulation. Case presentation: The present study describes a case of a 3-year-old girl with a giant cerebellar dermoid cyst, which initially manifested as hydrocephalus. Discussion: We discuss its epidemiological characteristics as well as diagnostic and therapeutic management. The combination of high clinical suspicion, anamnesis, thorough physical examination, and adequate interpretation of neuroimaging data is crucial for the early diagnosis and timely therapeutic intervention for such cysts. Conclusion: Surgical approach involving complete lesion resection considerably improves prognosis.